Penggunaan Asisten AI Untuk Meningkatkan Kemampuan Menulis Proposal Penelitian Siswa SMAIT As-Syifa Boarding School Subang - Rikki Faisal Heryana (Journal of Education and Social Culture, 2026)
This study aims to improve research proposal writing skills by utilizing AI Assistants. The research was conducted at SMAIT As-Syifa Boarding School Subang, involving twelfth-grade students. The method used is Classroom Action Research (CAR), implemented in two cycles, with each cycle consisting of planning, implementation, observation, and reflection. In the first cycle, the results showed an average student score of 41.2, with no students meeting the Minimum Completion Criteria (KKM), indicating that the research proposal writing lesson did not meet the target. After applying more targeted feedback and interactive teaching strategies in the second cycle, there was a significant improvement. In the second cycle, 100% of the students met the KKM, and the average score increased to 87. The results of this study indicate that the use of AI assistants can effectively enhance the research proposal writing skills of twelfth-grade students, making this technology a valuable tool to support a more effective and efficient teaching and learning process.